Determination of the Redox Potential for Aqueous Fe(Ⅱ)-Goethite Heterogeneous Systems by Potentiometric Method - Aiyu NIU; Xin LI; Fei LIU; Shanshan YANG (Yankuang ceshi)
The redox properties of Feaq 2+-iron oxide heterogeneous systems play an important role in the environmental behaviors of heavy metal and organic pollutants. However, the determination of Eh for heterogeneous systems is still challenging due to the redox equilibration between the electrode and suspension is sluggish. In this study, goethite was chosen as the representative of iron oxide in the aquifer. Both mediated and non-mediated potential methods were conducted to obtain the Eh of Feaq 2+-goethite heterogeneous system through the optimizing of measurement conditions. Moreover, the effect of the working electrode surface state, the kind of mediators, and the equilibrium time on the Eh measurement were investigated. The results indicated that the working electrode surface state, the suitable mediators, and the establishment of equilibrium were crucial for obtaining accurate Eh. Compared with the non-mediated potentiometric method, the mediated method can shorten the determination time, but the appropriate mediator must be chosen. In non-mediated potentiometric method, the equilibrium between the working electrode and goethite must be established. The standard redox potential (Eh0) of goethite with different particle sizes was obtained, which demonstrated the practicability of this method. The results provide the method for the Eh measurement of mineral heterogeneous systems, and also provide theoretical support for predicting the pollutant abiotic attenuation rate induced by Feaq 2+-iron oxide heterogeneous systems.